Effectiveness factors analysis of near-miss incidence referral in obstetric complications at Waras Wiris Andong General Hospital on Boyolali District - Edy Mustofa; Widyasih Pritasari; Arif Rahman Nurdianto; Sunarjo Sunarjo (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
AbstractMaternal mortality in Indonesia is still very high, and the biggest problem is obstetric complications. It is possible that the mother who has obstetric complications is safe and recovered (near miss) or died. This research was an observational analytic epidemiological study conducted to determine the effectiveness of near-miss incidence referral in obstetric complications using a cross-sectional approach. The sampling technique used was a random sampling system with 85 respondents. The effectiveness of referral affects near-miss incidence, meaning that mothers who get referral according to procedure only have a 0.107 times greater chance of not occurring near miss. Pregnant women who had a history of the disease had a risk of 0.157 times greater for the absence of near-miss than mothers who did not have a history. Pregnant women with high risk have 0.157 times no near-miss than those with low risk. Maternal antenatal examination affects the incidence of a near miss. It was found that the mother's history of illness, the risk of pregnancy owned by the mother and the effectiveness of referrals could affect the incidence of near miss in obstetric complications. In conclusion, there is an influence between the effectiveness of the referral and the near-miss incident at the Waras Wiris Andong Regional Hospital, Boyolali RegencyKeywords: referral, effectiveness, near-miss, obstetric complication